(untitled) (Voice of History, 2023)
Correction: on 24/07/2025 the title of the article on the website was updated to "Untouchability in Nepal: Historical Perspective". The title on the PDF was correct. This study tries to explore how the practice of untouchability developed in the ancient Indian Aryan society and over time entered Nepal and gradually took root in Nepali society. This study presents an argument based on historical facts that the practice of untouchability originated in the Indian Aryan society under the practice of some of the elites who had been in powerful positions. The practice was mainly instituted by the elites to continue exercising their power to subjugate the powerless. As the same, elite Aryans started migrating to Nepal during the ancient period, they brought with them the same practice to continue exercising self-acquired power within the Nepali society. But there was no strongly practiced untouchability in ancient Nepali society. The practice was slowly instituted with the adoption of associated rituals and traditions. The main objective of this study is to explore and analyze untouchability from a historical perspective. The custom of untouchability has existed in Nepal for centuries, there is limited historical evidence of any efforts to abolish it during the ancient and medieval periods. This study combines a qualitative research approach and a historical framework to explore the connection between a social norm and its history.